Maturidade sexual, lateralidade e dimorfismo sexual do caranguejo dulcícola dilocarcinus pagei no Sudeste do Brasil - Davanso, Thiago Maia [UNESP]; Taddei, Fabiano Gazzi; Hirose, Gustavo Luis; da Costa, Rogerio Caetano [UNESP] (Boletim do Instituto de Pesca, 2016)
This study estimated the sexual maturity of Dilocarcinus pagei Stimpson, 1861 based on relative growth and gonadal development. In addition, a possible sexual dimorphism was reported. The specimens were monthly captured from October 2005 to September 2007 in the Marimbondo/Furnas Hydroelectric Plant Reservoir, municipality of Icem in northwestern São Paulo State. Handedness was recorded for males, with the right cheliped propodus invariably longer and wider than the left. The estimated carapace width for morphological sexual maturity in males was 28.7 mm, based on the biometric relationship of the cheliped propodus length vs. carapace width; for females, this value was 24.2 mm, using the relationship of the abdominal width vs. carapace width. The size at gonadal maturity was estimated at 39.2 mm and 39.9 mm, for males and females respectively (CW50). There was not sexual dimorphism in relation to carapace width. For a crab to be able to procreate, it must reach morphological maturity and have developed gonads. Thus a minimum capture size based on the size, at which 50% of the population is considered reproductive, can ensure the continued preservation of this species.
Sexual maturity, handedness and sexual dimorphism of the freshwater crab dilocarcinus pagei in Southeastern Brazil
Keywords: Allometry; Gonadal maturity; Morphological maturity; Reproduction